Analisis Framing Berita Kekerasan Berbasis Gender Online di Media Liputan6.com dan Antaranews.com - Zikrina Munawarah (Airlangga University, 2024)
This research aims to conduct a framing analysis of online gender-based violence (GBV) news presented by two prominent online media platforms in Indonesia, namely Liputan6.com and Antaranews.com. The phenomenon of online GBV has become increasingly significant with the growth of internet users and social media. In the context of the pandemic, the CATAHU report from the National Commission on Violence Against Women (Komnas Perempuan) indicates a dramatic increase in online GBV cases. This study adopts the framing analysis model proposed by Robert Entman to investigate how media framing constructions influence the public's understanding and perception of the online GBV issue. Liputan6.com focuses its reporting on online GBV in general, while Antaranews.com is more focused on the context of violence against female consumers by